ANALISIS KELAYAKAN INVESTASI ALAT ROLL STREAPING PADA UKM MEKAR HANDCRAFT - Ahmad Zaini (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
UKM "Mekar Handcraft" produces woven bags. The initial process involves cutting the strings using a manual tool made of wooden blocks with nails. Then, a rolling streaping tool is used, but it faces a constraint where some raw materials cannot be spun using the spinning tool, so a manual tool is used instead. Additionally, the proximity of the raw material to the roll area is too close, resulting in frequent string breakage. The introduction of this new streaping tool innovation is expected to accelerate the production process. An investment feasibility analysis is needed to determine the viability of this investment. Based on the research, the Net Present Value (NPV) is calculated to be (Rp.212,450), which is greater than 0, indicating that the investment is viable. However, the Internal Rate of Return (IRR) calculation yields a value of 11.29%, which is less than the Minimum Acceptable Attractive Rate (MAAR) of 20%, indicating that the investment is not viable. The Payback Period calculation results in 10.78 months, indicating a relatively fast return on investment, making it a viable investment. Furthermore, the Profitability Index (PI) calculation yields a value of 1.11, which is greater than 1, indicating that the investment is viable